Efektivitas Implementasi Pelayanan Surabaya Single Windows Studi Kasus Kelurahan Rungkut Tengah - Wahyu Arpa Ramayanti; Riskya Dwijayanti (Politeknik Kampar, 2023)
This research aims to determine the effectiveness of the implementation of the Surabaya Sigle Windows Service in Rungkut Tenagh Village. The method used is qualitative research with data collection techniques through interviews and field observations. The research results show that in general, the Surabaya Single Windows Service program in Rungkut Tengah Subdistrict can be said to be effective because it has provided benefits to residents, especially in terms of procurement and maintenance of public facilities such as roads, parks and fields. However, there are still several obstacles that need to be overcome, such as the lack of socialization about the program and the lack of transparency and accountability of SSW Alfa Surabaya in managing the program. Therefore, there needs to be more intensive efforts in socializing the SSW Alfa program in order to understand the community benefits of this program and a more transparent and accountable mechanism in managing this program. In implementing the Surabaya Single Windows Service program, cultural and social factors also influence the effectiveness of the program. Different mindsets and cultures among citizens can influence perceptions of programs and participation in programs. Therefore, efforts are needed to pay attention to cultural and social factors in the environment.